Perlindungan Hukum Terhadap Konsumen Pengguna Pinjaman Online Berbasis Financial Technology oleh Otoritas Jasa Keuangan - Yulenrivo, Fakhri; Azheri, Busyra; Yulfasni, Yulfasni (UNES Law Review, 2023)
Online loans are a common thing that occurs among the wider community today, one of which is legal and illegal online loans. The easy conditions for applying for a loan make many people tempted to apply for a loan, where with just a photo of their KTP and filling in their data, everyone can easily get funds quickly. OJK is an independent organization, free from interference from other parties, whose function is to provide an integrated regulatory and supervisory system for all activities in the financial services sector as well as providing legal defense as regulated in OJK Law no. 21/2011 Articles 28, 29, and 30. As well as in POJK No. 31/2020 and POJK No. 6/2022. The method in this research uses a normative and qualitative approach. The main data in this research is secondary data obtained from library materials or literature that is related to the research object. The research results obtained: 1. Legal protection for consumers using online loans based on financial technology in the laws and regulations that can be implemented, namely: preventive and repressive legal protection. 2. Legal/licensed online loans are under the supervision of the OJK and regulated by POJK Number 10/POJK.05/2022 concerning Information Technology-Based Joint Funding Services (POJK 10/2022).